Monetary Policy Collision and Banking Index: Perspective Study of InfoBank15 Index in Indonesia Stock Exchange - Ardhiani Fadila (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This paper reveals evidence on the nexus between monetary policy and banking index performance in Indonesia Stock Exchange. Specifically, this study examines the effect of interest rate, inflation, money supply, and exchange rate as monetary policy variables. The dependent variable is measured by infobank15 index. This research employed secondary data covering period 2015-2020. The VAR/VECM method was used to demonstrate the causality dan co-integration of studied variables. The outcomes suggest that money supply has positive significant with infobank15 index both in short-term and long-term relationship. Further, the statistical results indicates that inflation gives biggest shock in the long-term. This paper helps in giving suggestions to the central bank, researchers, banking companies and other financial institutions to look into monetary policy rates and central bank also can concern on the macro-economic situation in the country.